Lesions and Distribution of Viral Antigen in the Brain of Hamsters Infected With Equine Herpesvirus (EHV)–9, EHV-1 Strain Ab4p, and Zebra-Borne EHV-1. Issue 5 (September 2019) - El-Habashi, Nagwan; El-Nahass, EL-Shaymaa; Abd-Ellatieff, Hoda; Saleh, Asmaa; Abas, Osama; Tsuchiya, Yuya; Fukushi, Hideto; Yanai, Tokuma
Encephalitis in hamsters, which was induced by equine herpesvirus (EHV)–9, EHV-1 strain Ab4p, and zebra-borne EHV-1, was investigated and compared to assess viral kinetics and identify the progression and severity of neuropathological findings. Hamsters were inoculated with EHV-9, EHV-1 strain Ab4p, and zebra-borne EHV-1 via the nasal route and euthanized at 24, 48, 72, 96, 120, 144, and 168 hours postinoculation (HPI). The inoculated hamsters had mild to severe neurological signs at 60 to 72, 96, and 120 HPI, and the mortality rate was 75%, 0%, and 0% for animals inoculated with EHV-9, EHV-1 strain Ab4p, and zebra-borne EHV-1 viruses, respectively. Inoculated hamsters had varying degrees of rhinitis and lymphoplasmacytic meningoencephalitis, as well as differences in the severity and distribution of cerebral lesions. Furthermore, the cellular distribution of viral antigen depended on the inoculated virus. Neuronal necrosis was widely detected in animals inoculated with EHV-9, while marked perivascular cuffs of infiltrating inflammatory cells and gliosis were detected in animals inoculated with EHV-1 strain Ab4p and zebra-borne EHV-1. In the present study, 3 viruses belonging to the herpesvirus family induced encephalitis after initial propagation in the nasal cavity. These viruses might travel to the brain via the olfactory pathway and/or trigeminal nerve, showing different distributions and severities of neuropathological changes.